Fabrication and characterization of aluminum-carbon nanotubes (Al-CNT) functionally graded cylinders - Morad, Sherry Samy (AUC Knowledge Fountain, 2016)
Attention to carbon nanotubes (CNT) reinforced aluminum matrix composites has been growing considerably for the past decade owing to the expected improvement in specific properties that this nano-composite could offer. Functionally graded material (FGM), is also a rapidly developing field of materials science offering the possibility to manufacture components with desired properties at selective locations to serve different applications. Nano FGMs are the newest generation of this class of materials that is currently being theoretically researched intensely with more requirement for experimental research to support and verify the theoretical and numerical models. In the current research, an experimental study was conducted to develop a route to fabricate Al-CNT functionally graded cylinders varying materials along radial direction. Larger content of CNT reinforcement was selectively used at the outer layers to provide the highest strength, hardness and wear resistance at the surface subjected to higher stresses and more severe environments. Pure Al was chosen as the core material since it is subjected to lower stresses and to provide overall ductility to the material. The gradient selected is also cost effective as the expensive CNT is placed only in the layers that require most strengthening while maintaining a soft tough core leading to a balanced set of properties. The produced specimens having increased strength and hardness at the surface in addition to overall combination of high strength, ductility and light weight, together with the cylindrical geometry of the produced FGMs could be used in various applications especially mobility related applications such as drive shafts for aerospace and automotive industries. Testing and characterization of the produced samples were carried out to evaluate the performance of the cylindrical FGMs and the interfacial bonding between the different layers. Two sets of functionally graded specimens were produced; first is “FG2%” having the 2%CNT-Al at the surface then followed by layers of 1%CNT-Al, milled Al and reaching pure Al at the core. The second is “FG5%” having the 5%CNT-Al at the surface then followed by layers of 2%CNT-Al, milled Al and reaching pure Al at the core. Two specifically designed molds were manufactured to produce the functionally graded cylinders; mold A and mold B with enhancements implemented in mold B to produce well bonded cylindrical FGMs. Al-CNT composite powders with 1, 2, 5wt.% CNT fraction as well as milled Al were manufactured deploying planetary high energy ball milling technique (HEBM) of powders of CNT and Al. These were loaded in the designated layers of the manufactured molds. Powder metallurgy process was followed; starting with cold compaction and followed by sintering, then hot extrusion to produce compacts of Al-CNT FGMs of high density. Mechanical testing and characterization were carried out on the produced specimens and these included; mechanical compression, tension, optical microscopy, scanning electron microscopy as well as nanoindentation. It was concluded that the developed route and novel manufactured molds were successful to produce well bonded functionally graded cylindrical structures of Al-CNT. Adding CNT to Al reaching 2%wt. CNT at the outer layer with varying composition to reach pure Al at the core resulted in very unique balanced properties. The samples showed high strength while retaining a higher percentage of the material ductility compared to pure Al and homogeneous composite competitor having the same overall CNT content. The compression strength and hardness values also showed significant enhancement. Increase in content of CNT up to 5%wt. showed a remarkable increase in compression strength and hardness with some enhancement in modulus of elasticity. However, its full potential of strength and ductility could not be confirmed in this study due to fracture of the specimens under tension outside the gauge length. This could be due to increased sample notch sensitivity or increased internal stresses between layers as CNT percentage increases.